English Teaching Assistance Employing the Multiple Intelligences Theory to Kasih Bangsa Elementary School Students - Trisnowati Tanto; Maryani Maryani; Jeanyfer Tanusy; Vanessa Laurensa; Denny Linggar (Journal of Innovation and Community Engagement, 2024)
Considering that English is not the main language in Indonesia, an effective teaching method at school is crucial to students' ability to speak English fluently. However, in reality, many teachers still depend on conventional teaching methods. Therefore, this teaching assistance aims to facilitate Kasih Bangsa Elementary School students with a method that considers students' overall intelligence adapted from the Multiple Intelligences theory proposed by Howard Gardner, who argues that a person can have more than one intelligence. Furthermore, this teaching assistance is based on the Community-Based Participatory Research (CBPR) method, which focuses on the collaboration between researchers and communities. The program consists of three main processes: an interview with teachers of Kasih Bangsa Elementary School, a workshop on Multiple Intelligences Theory for the teachers, and a teaching demonstration by some of the students of the English Department, Maranatha Christian University. From this teaching assistance, the Multiple Intelligences theory is proven to improve the learning quality and boost students' motivation effectively.